(t+4)(t+4)=54

Simple and best practice solution for (t+4)(t+4)=54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t+4)(t+4)=54 equation:


Simplifying
(t + 4)(t + 4) = 54

Reorder the terms:
(4 + t)(t + 4) = 54

Reorder the terms:
(4 + t)(4 + t) = 54

Multiply (4 + t) * (4 + t)
(4(4 + t) + t(4 + t)) = 54
((4 * 4 + t * 4) + t(4 + t)) = 54
((16 + 4t) + t(4 + t)) = 54
(16 + 4t + (4 * t + t * t)) = 54
(16 + 4t + (4t + t2)) = 54

Combine like terms: 4t + 4t = 8t
(16 + 8t + t2) = 54

Solving
16 + 8t + t2 = 54

Solving for variable 't'.

Reorder the terms:
16 + -54 + 8t + t2 = 54 + -54

Combine like terms: 16 + -54 = -38
-38 + 8t + t2 = 54 + -54

Combine like terms: 54 + -54 = 0
-38 + 8t + t2 = 0

Begin completing the square.

Move the constant term to the right:

Add '38' to each side of the equation.
-38 + 8t + 38 + t2 = 0 + 38

Reorder the terms:
-38 + 38 + 8t + t2 = 0 + 38

Combine like terms: -38 + 38 = 0
0 + 8t + t2 = 0 + 38
8t + t2 = 0 + 38

Combine like terms: 0 + 38 = 38
8t + t2 = 38

The t term is 8t.  Take half its coefficient (4).
Square it (16) and add it to both sides.

Add '16' to each side of the equation.
8t + 16 + t2 = 38 + 16

Reorder the terms:
16 + 8t + t2 = 38 + 16

Combine like terms: 38 + 16 = 54
16 + 8t + t2 = 54

Factor a perfect square on the left side:
(t + 4)(t + 4) = 54

Calculate the square root of the right side: 7.348469228

Break this problem into two subproblems by setting 
(t + 4) equal to 7.348469228 and -7.348469228.

Subproblem 1

t + 4 = 7.348469228 Simplifying t + 4 = 7.348469228 Reorder the terms: 4 + t = 7.348469228 Solving 4 + t = 7.348469228 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + t = 7.348469228 + -4 Combine like terms: 4 + -4 = 0 0 + t = 7.348469228 + -4 t = 7.348469228 + -4 Combine like terms: 7.348469228 + -4 = 3.348469228 t = 3.348469228 Simplifying t = 3.348469228

Subproblem 2

t + 4 = -7.348469228 Simplifying t + 4 = -7.348469228 Reorder the terms: 4 + t = -7.348469228 Solving 4 + t = -7.348469228 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + t = -7.348469228 + -4 Combine like terms: 4 + -4 = 0 0 + t = -7.348469228 + -4 t = -7.348469228 + -4 Combine like terms: -7.348469228 + -4 = -11.348469228 t = -11.348469228 Simplifying t = -11.348469228

Solution

The solution to the problem is based on the solutions from the subproblems. t = {3.348469228, -11.348469228}

See similar equations:

| -27x=81 | | 142.5*20=91 | | 142.5*91=20 | | x=400+-1y | | 6x+18=12-9 | | 142.5*91=20*x | | 8x+21=6x+69 | | 2x-4=7x-7-5x | | 142.5=20*91 | | 4x+35=14x+45 | | 0.7x=0.9+0.2x | | -4+2x=-8+24 | | 7y+10=2y+25 | | 4x+21=5x | | 1x+1y=400 | | 8.2x+24.88=-11.8x+24.10 | | 5x+3x=20x | | 11j+29+13j-12= | | (x-3)(x-4)(x-7)=0 | | (z+6)(z+6)=-4 | | 5ln(3x)-2=12 | | 6t-5=3t+6 | | (2u+3)(5+u)=0 | | 4x+2=-x+12 | | .70x+.35(120)=.35(96) | | 2z=i(2+9i) | | 2x^214=102 | | .25x+.15y=19 | | G=um | | P(X)=200-0.2x | | .4x+x=1250 | | (x-1)*dy=2x^3y*dx |

Equations solver categories